Dictionnaire raisonné universel d'histoire naturelle : contenant l'histoire des animaux, des végétaux et des minéraux, et celle des corps célestes, des météores, & des autres principaux phénomenes de la nature ; avec l'histoire et la description des drogues simples tirées des trois regnes ; et le détail de leurs usages dans la médecine, dans l'économie domestique & champêtre, et dans les arts & métiers : plus, une table concordante des noms latins, & le renvoi aux objets mentionnés dans cet ouvrage / par M. Valmont de Bomare ... - Valmont-Bomare, M. (Jacques Christophe), 1731-1807. (Tufts University. Tisch Library., 2015)
Volume 1 of 6.; Nouvelle édition, revue & considérablement augmentée par l'auteur ; tome premier[-sixieme].; 1 online resource (6 v. (xxiij, [1], 768; [4], 854, [2]; [4], 704; [4], 852; [4], 901, [3]; [4], 560, CCXXXII p., [1] leaf of plate) : ill., coat of arms (engravings); The same edition also issued in the same year in octavo format (in nine volumes). Cf. Wellcome cat. of printed books, V, p. 329.; Printers from colophons of each volume: vol. 1, 4, 5: Stoupe; vol. 2: Demonville; vol. 3: Didot; vol. 6: printer not indicated.; Dedicated to Prince de Condé.; Engraved frontispiece signed: B.L. Prevost sculp.; Head- and tail-pieces; initials.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Binding: Tufts print copy: Bound uniformly in contemporary mottled calf.; Indexed in: Blake, J. NLM 18th cent.,p. 468